Livelihood and food acquisition challenges in island communities during the global pandemic - Farisal Ungkakay-Bagsit; Mary Barby P. Badayos-Jover; Raymundo R. Pavo; Pearlyn Cambronero-Tumabiao (Marine and Fishery Sciences)
The COVID-19 pandemic has greatly affected the global economy and efforts toward achieving food security. Fisheries was one of the vulnerable sectors to COVID-19 impacts but available literature on this is limited mostly to accessible areas. Hence, this study focuses on island communities in remote areas in northern Iloilo, Philippines, to understand their unique experiences with access to natural resources, livelihood services and food during the COVID-19 pandemic. Household surveys (n = 520), key-informant interviews (n = 10) and focus group discussions (n = 51) were performed. It was found that 70% of respondents depended on fisheries-related livelihoods, such as fishing and post-harvest activities. The other 30% of respondents depended on contractual jobs, small businesses, remittances from family members, farming, and boat transport services. Generally, remote-island villages had difficulty accessing natural resources as shown by lesser fishing operations (~ 0-20 days month-1), limited access to livelihood inputs (e.g. crude oil and ice), and limited access to markets/ports because of restricted operating hours during the pandemic. Financial hardships and travel restrictions made access to non-fisheries food products (e.g. rice, vegetables, and meat) very difficult. The access to freshwater was also an issue because water supply come from other islands or the mainland. Overall, results showed that the COVID-19 pandemic has severely affected the livelihoods and food security of inhabitants of remote island villages. These findings are valuable for future emergency management measures especially to ensure that no one is left behind.